PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU) DAN DANA ALOKASI KHUSUS (DAK) TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH KABUPATEN BANYUWANGI TAHUN PERIODE 2012 – 2016 - Nuro, Septina; Widiastoeti, Hendy (Universitas 17 Agustus 1945 Surabaya, 2019)
ABSTRACTThe purpose of this research is to know whether there is influence of Local Original Income (PAD), General Allocation Fund (DAU) and Special Allocation Fund (DAK) to the level of Financial Independence of Banyuwangi Regency year 2012 - 2016 either partially or simultaneously. The population in this research is Banyuwangi Regency using secondary data in the form of Budget Realization Report (BRR) of Banyuwangi Regency in 2012 - 2016. Hypothesis testing in this research use multiple linear regression with t test, F test and coefficient of determination. The data that have been collected is analyzed first by testing the classical assumption then hypothesis tested by SPSS 20.0. Based on the research results can be concluded that the partial variable PAD has a significant effect, while the variable DAU and DAK have no significant effect on the level of regional financial independence. Simultaneously, PAD, DAU and DAK variables significantly influence the level of local financial independence. Keywords:Local Own Revenue, General Allocation Fund, Special Allocation Fund and Local Financial Independence Level.